The prognostic value of endoglin (CD105) expression in ovarian carcinoma. Issue 5 (1st September 2006) - Taskiran, C.; Erdem, O.; Onan, A.; Arisoy, O.; Acar, A.; Vural, C.; Erdem, M.; Ataoglu, O.; Guner, H.
Abstract : Intratumoral angiogenesis has become an important issue after the identification of antiangiogenic therapeutics. The purpose of this study was to investigate the prognostic value of CD105 in patients with ovarian cancer and also to compare with CD31. Fifty-eight patients were included to this study. All the paraffin blocks were reviewed, and angiogenesis was determined by immunohistochemical staining, using anti–CD105 and anti-CD31 monoclonal antibodies. The mean microvessel density (MVD) with CD105 and CD31 were 28.78 ± 22.20 and 28.69 ± 18.57, respectively ( P = 0.97). With respect to prognostic factors, CD31 was only significant for suboptimal cytoreduction ( P = 0.02), and CD105 was significant for both advanced stage and suboptimal cytoreduction ( P = 0.02 and P = 0.05, respectively). For survival analysis, patients were divided into three groups by quartiles for each marker (group 1, <25%; group 2, 25–75%; and group 3, >75%). By CD31, only significant difference was noted between group 1 and group 2 ( P = 0.03). In analysis with CD105, the survival rate of patients with group 3 was significantly worse than group 1 and group 2 ( P = 0.01 for both). In multivariate analysis, cytoreduction and MVD determined by CD105 remained significant. In this study, endoglin was found to be an independent predictor of poor survival. Therefore, it could be used for antiangiogenic therapies.